2014
DOI: 10.1038/eye.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Corneal sensitivity and morphology of the corneal subbasal nerve plexus in primary congenital glaucoma

Abstract: Background To quantify the corneal subbasal nerve density and the total number of nerve fibers in primary congenital glaucoma (PCG) and to evaluate their impact on corneal sensitivity. Methods Forty eyes of 26 PCG patients were compared with 40 eyes randomly selected from 40 non-glaucoma patients who populated the control group. Central corneal sensitivity (CCS) was assessed by means of Cochet-Bonnet esthesiometry. The mean subbasal nerve density and the total number of nerve fibers were quantified by lasersca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Mean CTT was slightly lower in glaucomatous eyes relative to normal eyes; however, the difference was not statistically significant, and the values obtained in our study are generally similar to previously published ranges in normal cats . Similar findings were reported in prior studies involving human PCG patients . Prior studies in human patients have shown that buphthalmos at an early age may be associated with significant reduction in corneal sensitivity, although in these patients, increased CD is also associated with increased CT and corneal edema .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mean CTT was slightly lower in glaucomatous eyes relative to normal eyes; however, the difference was not statistically significant, and the values obtained in our study are generally similar to previously published ranges in normal cats . Similar findings were reported in prior studies involving human PCG patients . Prior studies in human patients have shown that buphthalmos at an early age may be associated with significant reduction in corneal sensitivity, although in these patients, increased CD is also associated with increased CT and corneal edema .…”
Section: Discussionsupporting
confidence: 88%
“…In their study involving patients aged 8 to 16 years old with PCG, Gatzioufas et al identified significant reduction in mean corneal sub‐basal nerve density and total number of nerve fibers in the central cornea. Although number and density of corneal sub‐basal nerve fibers were positively correlated with corneal sensitivity, corneal sensitivity was not demonstrably reduced in PCG eyes in that study …”
Section: Introductionmentioning
confidence: 53%
“…Sometimes it is difficult to distinguish age‐specific alterations from degenerative modifications due to environmental and genetic factors. A considerable number of studies have attempted to demonstrate the changes occurring in corneal innervations (with particular regard to the density of nerves related to age (Dehghani et al, ; Gatzioufas et al, ). Corneal images acquired by in vivo specular and CM provide clinical information on the health of the cornea endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…; Gatzioufas et al. ). In cases where corneal manifestations of neurotrophic keratitis are present, corneal sensations are also reduced as is corneal nerve density (Benitez‐Del‐Castillo et al.…”
Section: Discussionmentioning
confidence: 97%
“…Preservation of the nerves and their neurons in the trigeminal ganglion would thus continue to provide a positive neurotrophic effect at the ocular surface. It is generally known that corneal sensitivity does not correlate well with sub-basal nerve density (Patel et al 2009;Gatzioufas et al 2014). In cases where corneal manifestations of neurotrophic keratitis are present, corneal sensations are also reduced as is corneal nerve density (Benitez-Del-Castillo et al 2007;Hamrah et al 2010;Labbe et al 2012), but there are instances where corneal sensations are completely absent in the presence of normal sub-basal nerve density (Dhillon et al 2014).…”
Section: Discussionmentioning
confidence: 99%